Sovereign vs. corporate debt and default: More similar than you think - Gita Gopinath; Josefin Meyer; Carmen M. Reinhart; Christoph Trebesch (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Theory suggests that corporate and sovereign bonds are fundamentally different, also because sovereign debt has no bankruptcy mechanism and is hard to enforce. We show empirically that the two assets are more similar than you think, at least when it comes to high-yield bonds over the past 20 years. Based on rich new data we compare risky US corporate bonds ("junk" bonds) to risky emerging market sovereign bonds 2002-2021 (EMBI bonds). Investor experiences in these two asset classes were surprisingly aligned, with (i) similar average excess returns, (ii) similar average risk-return patterns (Sharpe ratios), (iii) a similar default frequency, and (iv) comparable haircuts. A notable difference is that the average default duration is higher for sovereigns. Furthermore, the time profile of bond returns and default events differs. One explanation is that the two markets co-move differently with domestic and global factors. US "junk" bond yields are more closely linked to US market conditions such as US stock market returns, US stock price volatility (VIX), US industrial production, or US monetary policy.
Keywords: G1; G3; H6; 330; Sovereign debt and default; Default Risk; corporate bonds; corporate default; junkbonds; Chapter 11; crisis resolution